Uji Plagiarism pada Tugas Mahasiswa Menggunakan Algoritma Winnowing - Moh Sadly Ramli; Sugiarto Cokrowibowo; Muh Fahmi Rustan (Indonesian Society of Applied Science, 2021)
Plagiarism is the act of taking or plagiarizing the work, ideas or ideas of others either intentionally or unintentionally and claiming to be one's own work without mentioning the source or author. Often students plagiarize assignments given by the lecturer so that sometimes students just copy other people's assignments to complete the assignment. So that this can lead to dependence on other people in doing assignments and not being able to independently carry out assignments given by the lecturer. Currently, many plagiarism detection systems have been created to help reduce the level of plagiarism, one of which is the winnowing algorithm. In this study the authors used the winnowing algorithm to detect plagiarism in student assignments, namely programming source code, from the results of research conducted on 10 student assignments using the winnowing algorithm produced various similarity values as a percentage of similarity between two students tasks compared. With an average value of the overall similarity of the 10 tasks, namely 75.12%.